DOMESTIC LABOR LAW AFTER LC 150/2015 - Buriti, Adélia Araújo (2021)
The research examines the legal protection to domestic work before and after the promulgation of Complementary Law # 150/2015, taking as a case study the judicial demands of the Labor Court of Quixadá, in the Sertão Central of the state of Ceará, Brazil. The study starts analyzing the regulation of domestic work in Brazil. The first chapter deals with the historical context in which domestic work was developed: its relation to slavery, the promulgation of the 1988 Federal Constitution, the ratification of ILO Convention 189 by Brazil, and the approval of Complementary Law # 150/2015. The second chapter examines the domestic labor market, its characteristics and vulnerabilities, including the ones evidenced by the covid-19 pandemic. The third section identifies the data on the judicial demands of domestic workers, having as a case study the Labor Court in Quixadá, analyzing the rights required by workers, the profiles of workers and employers and the resolution given by the Labor Court. As for the methodological aspects, the dissertation uses the bibliographic and documentary, pure, quantitative and qualitative, descriptive and exploratory research methods. It concludes that LC 150/2015 has not yet reached the appropriate level of effectiveness in the Sertão Central, suggesting that regulation alone is not sufficient to ensure legal protection for domestic workers. The research identifies the domestic workers’ collective organization as an essential step for affirming these workers as subjects in the fights for the conquest and enforcement of rights.